The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1207/s15327914nc4802_10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Sulforaphane-Induced Cell Cycle Arrest and Apoptosis in Human Colon Cancer Cells

Abstract: Sulforaphane (SFN) is a natural micronutrient found in cruciferous vegetables that has been shown to possess antitumoral properties in carcinogen-treated rats. In vitro, SFN regulates phase II enzymes, cell cycle, and apoptosis. In the present study, we investigated the relationship between SFN induction of apoptosis and cell cycle arrest in HT29 human colon carcinoma cells. In previously published data, a significant increase in the G2/M phase of the cell cycle has been observed in SFN-treated cells that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 36 publications
5
79
1
3
Order By: Relevance
“…Further work established an IC 50 of 15 μM SFN in HT-29 cells and 50 μM in CaCo-2 cells, suggesting possible selective effects toward undifferentiated versus differentiated cells, respectively [36]. Alterations in cell cycle progression also have been reported in HT-29 cells treated with SFN, with a decrease in the percentage of cells in G1 and an increase in G2/M, as well as increases in cyclin A and cyclin B1 protein levels [37], and hyperphosphorylation of the retinoblastoma tumor suppressor protein (Rb) [38]. Furthermore, there was an increase in Bax protein expression, loss of cytochrome c from mitochondria, and concomitant elevation of cytosolic cytochrome c [37].…”
Section: Induction Of Cell Cycle Arrest And/or Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Further work established an IC 50 of 15 μM SFN in HT-29 cells and 50 μM in CaCo-2 cells, suggesting possible selective effects toward undifferentiated versus differentiated cells, respectively [36]. Alterations in cell cycle progression also have been reported in HT-29 cells treated with SFN, with a decrease in the percentage of cells in G1 and an increase in G2/M, as well as increases in cyclin A and cyclin B1 protein levels [37], and hyperphosphorylation of the retinoblastoma tumor suppressor protein (Rb) [38]. Furthermore, there was an increase in Bax protein expression, loss of cytochrome c from mitochondria, and concomitant elevation of cytosolic cytochrome c [37].…”
Section: Induction Of Cell Cycle Arrest And/or Apoptosismentioning
confidence: 99%
“…First, two groups demonstrated that SFN maintains Cdc2 kinase in its active form, which was correlated with induction of apoptosis [38,43]. However, another study reported reduction of Cdc25C, a phosphatase responsible for activation of Cdc2; this reduction of Cdc25C by SFN was mediated via activation of checkpoint 2 kinase (Chk2) [41].…”
Section: Induction Of Cell Cycle Arrest And/or Apoptosismentioning
confidence: 99%
“…In the last decade, many studies revealed that sulforaphane acts as a chemopreventive agent by inducing apoptosis and cell cycle arrest and inhibiting proliferation. In colon cancer cells, sulforaphane induced apoptosis and G2/M phase cell cycle arrest (15)(16)(17)(18)(19). In vivo studies showed that sulforaphane suppressed azoxymethane-induced colonic aberrant crypt foci (ACF) (20) and prevented polyps in Apc/Min mice (21).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of fruits and vegetables, along with extra-virgin olive oil, red wine, aromatic herbs (oregano, parsley, and rosemary), garlic, onion, and pepper (ingredients generously used in Mediterranean cuisine), ofers a number of phenolic compounds with a strong antioxidant action that is hardly possible to achieve with other types of diet. Examples are allyl sulides, which are present in garlic and raw onions, give cardiovascular beneits, improve cognitive ability, and have chemopreventive activity; it was shown that certain isothiocyanates (degradation products of glucosinolates, compounds present in caper berries) can afect the cell cycle and induce apoptosis in HT-29 human colon cancer cells and other isothiocyanates, present in high concentration in cruciferous vegetables (cabbage and broccoli) [24,25], have the capacity to modulate the metabolism of carcinogens; kaemferolo and lavonoids quercetin and hydrocinnamic acids from capers have well-known anti-inlammatory and antioxidant efects and chives also rich in phenolic compounds with diuretic, antihypertensive, anti-inlammatory, and antioxidant substances [26][27][28]; catechins fruit (e.g., apple skin and grape) antioxidant molecules prevent the production of reactive oxygen species generated by oxidative stress; the anthocyanins, plant pigments, give the red or blue color to fruits and vegetables (berries, eggplant, black grapes, and red beet), are antioxidants, photoprotective, and are able to inhibit angiogenesis. One other major constituent of MD is vitamin E, which contains a group of eight isomers: four tocopherols (α, β, γ, δ-tocopherol) and four tocotrienols (α, β, γ, δ-tocotrienol).…”
Section: Antioxidantsmentioning
confidence: 99%